JAM’UL QUR’AN PADA MASA NABI DAN PARA SAHABAT KAJIAN HISTORIS TENTANG PROSES PENGUMPULAN BESERTA AUTENTISITASNYA - Muhammad Widinur Caronge; Achmad Abubakar; Halimah Basri (LPPM STAI Muhammadiyah Probolinggo, 2025)
This study examines the process of Jam‘ul Qur’an during the time of the Prophet Muhammad ﷺ and his companions, focusing on the historical context of revelation, the system of collection, and the authenticity of the mushaf. The findings show that the codification of the Al-Qur’an began gradually during the Prophet’s lifetime rather than after his death. This process operated through the institution of revelation, with the Prophet as the authoritative recipient, Gabriel as the transmitter, the kuttāb al-wahy as scribes, and the companions’ collective memorization as guardians of oral transmission. During the era of the Khulafā’ ar-Rāshidīn, codification progressed through two major phases that is the initial compilation of the mushaf under Abu Bakar as-Ṣiddīq and the standardization of the text under ‘Utsmān bin ‘Affān. Using qualitative methods and both classical and contemporary literature, the study affirms the Al-Qur’an’s authenticity through dual transmission channels mutawātir memorization and written documentation. Unlike earlier studies that emphasize a single codification period, this research provides a historical synthesis across phases and connects modern textual criticism with the epistemology of Islamic revelation. It concludes that the Al-Qur’an used today is an authentic continuation of the ‘Utsmānī codex, whose integrity has been preserved throughout history.